Straight talk on trade ideas for a sane world economy - Rodrik, Dani (Princeton University Press, 2018)
a"Rodrik takes globalization's cheerleaders to task, not for emphasizing economics over other values, but for practicing bad economics and ignoring the disciplineu2019s own nuances that should have called for caution. He makes a case for a pluralist world economy where nation-states retain sufficient autonomy to fashion their own social contracts and develop economic strategies tailored to their needs. Rather than calling for closed borders or defending protectionists, Rodrik shows how we can restore a sensible balance between national and global governance. Ranging over the recent experiences of advanced countries, the eurozone, and developing nations, Rodrik charts a way forward with new ideas about how to reconcile todayu2019s inequitable economic and technological trends with liberal democracy and social inclusion. Deftly navigating the tensions among globalization, national sovereignty, and democracy, Straight Talk on Trade presents an indispensable commentary on todayu2019s world economy and its dilemmas, and offers a visionary framework at a critical time when we need it most."--Provided by publisher.